PEMANFAATAN BUKU TEKS OLEH GURU EKONOMI SMA NEGERI SE-KABUPATEN OGAN ILIR - Yunita Leni Utari; Deskoni; Dewi Koryati (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2017)
This study discusses the use of textbooks by economics teacher based on curriculum 2013 high schools in Ogan Ilir. The formulation of the research problem are " What textbooks are used by the economics teacher in SMA Ogan Ilir district? Is there any consideration of economics teacher in selecting textbooks used in SMA Ogan Ilir district? What are the difficulties faced by teachers in the use of economic textbooks in SMA Ogan Ilir district?".The research method using descriptive method. The numbering subject are 5 peoples from economics teacher, consists of three teachers from SMA Negeri 1 Indralaya and two teachers from SMA Negeri 2 Tanjung Raja. The data of textbook used by economics teacher, teacher’s consideration in choosing textbook and the difficulties faced by economics teacher in using textbook were collected through questionnaires and intervew techniques. Each data is analyzed by using a percentage formula. The results of research on the use of textbook by High School economics teacher in Ogan Ilir district can be seen from indicators of the types of textbook. Teacher’s consideration in choosing textbook and the difficulties faced by teachers in using textbook show a good category. The instruments that used in the study are questionnaires, Guttman scale and interview. From this study, the researcher conclude that the use of by economics teacher in senior high school Ogan Ilir district included in good category. For the next research, is expected to examine the difficulties or limitations of textbooks in any material or any economics textbook chapters in senior high school in Ogan Ilir used by teachers based on the curriculum of 2013.